Are we living in an age of reason - Lyon, Thomas Eddy (My University, 1893)
Introduction: I see gathered before me here today, a body of people whose intellectual ability, I presume, would make a fair standard by which to measure the intelligence of like gatherings in any part of the civilized world. Yet, fellow-citizens and fellow-students, I believe, that were I to ask you this question this afternoon, nine-tenths of you would answer without the least hesitancy, we are! Let us see.
Citation: Lyon, Thomas Eddy. Are we living in an age of reason. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Intelligence; Intellectual; Reason; Civilized; Theses; Manuscripts (documents)